The Effect of Work-Life Balance and Workload on Employee Performance through Work Engagement - Lebrina Lorince Tangpen; Apryla Ayu Yega Putriani; I Made Suparta; I Dewa Ketut Raka Ardiana (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Human resources play a strategic role in determining organizational success, particularly in maintaining employee performance amid increasing job demands and business competition. This study aims to analyze the effect of work-life balance and workload on employee performance through work engagement as a mediating variable at PT Panca Mitra Multiperdana Tbk, Surabaya. This study uses a quantitative approach with an explanatory causal research design. Data were collected from 100 employees selected through purposive sampling and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results show that work-life balance and workload have a positive and significant effect on work engagement. Work engagement also has a positive and significant effect on employee performance. However, work-life balance and workload do not have a significant direct effect on employee performance. In addition, work engagement fully mediates the relationship between work-life balance and employee performance, as well as the relationship between workload and employee performance. The coefficient of determination (R²) indicates that the research model explains 77.1% of the variation in employee performance, which reflects strong predictive ability. The findings show that employee performance is more strongly influenced by work engagement than by work-life balance and workload directly. Therefore, organizations need to prioritize strategies that enhance work engagement by creating a proper work-life balance and managing workload effectively to improve employee performance.